[Commonplace book of prayers, amulets, and magic squares in Arabic and Turkish]. - ʻAbd al-Salām bin Mashīsh, 1163?-1225?; Hamadhānī, ʻAlī ibn Muḥammad, 1314-1385.; Shādhilī, Abū al-Ḥasan ʻAlī ibn ʻAbd Allāh, approximately 1196-1258.; Jazūlī, Muḥammad ibn Sulaymān, 1404-1465.; Sanūsī, Muḥammad ibn Yūsuf, approximately 1427-approximately 1490.; Sanūsī, Muḥammad ibn Yūsuf, approximately 1427-approximately 1490.; Ibn al-ʻArabī, 1165-1240.
A collection of prayers, amulets, and magic squares; extracts and a magic square on the the pastedowns.
29. fol. 73b-74a: [Short prayers, amulets and magic squares, in Arabic and Ottoman Turkish].
Ms. codex.
Physical description: 9-15 lines per page; written in naskh in black and red by different hands on tan Arabic paper. Catchwords; marginal notes and corrections. Qurʼānic verses and most prayers vocalized. Two inserts between fol. 34-35, one of which contains a magic square.
Brockelmann, C. GAL
Bouwman Oriental Books
Arabic and Ottoman Turkish.
Half leather with marbled paper covers and flap; yellow pastedowns.
Keywords: Amulets (Islam); Hadith -- Texts; Islam -- Prayers and devotions -- Early works to 1800.; Magic squares; Shādhilīyah -- Early works to 1800.; Manuscripts, Arabic; Manuscripts, Turkish; Commonplace books -- Islamic countries